If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x = 3x + -16 Reorder the terms: 10x = -16 + 3x Solving 10x = -16 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10x + -3x = -16 + 3x + -3x Combine like terms: 10x + -3x = 7x 7x = -16 + 3x + -3x Combine like terms: 3x + -3x = 0 7x = -16 + 0 7x = -16 Divide each side by '7'. x = -2.285714286 Simplifying x = -2.285714286
| -7b+4+4b=-4b+b | | 127-5x=2x+22 | | 15c-5c= | | 5x^2-9x-2= | | 100+.133x=x | | 12-a-a-a= | | (2x-8)=(x+3) | | 2y-2=6y-3 | | 8g-g= | | d+e+e+d+e= | | b+b+c+c+c= | | .2x-.5=.1x+7 | | 116-5x=40x+21 | | -3x+2x=-4+3x | | 10x=24-2x | | 14-10x=41-17x | | -19-8x=10x+17 | | 14-3p+8p=6p+6p | | 2x+13=-23-10x | | 4e^5x=24 | | 2x^2+18x=3 | | (4w-3)(5w-5)= | | 5k+5=6k+13 | | 97-3x=2x+22 | | 6x+5=69-2x | | 5A+2D= | | x^2-14x+6=0 | | 6+6x=36+x | | -4k^2-8k=-3-5k^2 | | 4x^2+8x-48=0 | | 6x-2=15x-38 | | 56-2x=8x+16 |